Menggali Potensi Non-Fungible Token (NFT) dalam Administrasi Pertanahan : Kajian di Provinsi DKI Jakarta - Khithobi, Arya Teges; Sari, Eka Ratna; Achfan, Nurul Azimah; Auliya, Ananda Islami; Rohmadani, Eka Suci; Ferdian Ariawantara, Putu Aditya (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Land is an important legal object that can be utilized by the community if it has the right to ownership of the land to be used. However, currently there are many land administration problems in various regions in Indonesia, one of which also occurs in the implementation of land administration in DKI Jakarta Province. From the existence of these problems, it can harm landowners in the DKI Jakarta Region. Researchers use qualitative research methods so that the research conducted can be more in-depth and accurate. The discussion found from this writing is that there are several problems that occur in land administration in DKI Jakarta, including the existence of people who do not use the land ownership publication system because there are still people who believe in the use of customary law, the emergence of land mafia actors who always falsify certificates for one's land ownership, and also problems in the form of KKN behavior carried out by several irresponsible land officials. On the basis of this, the author offers an NFT technology strategy, namely by digitizing land certificates by providing secret codes that will not be the same between one certificate and another. From the results of the research conducted by the author, the author concludes that there is potential for the implementation of NFT technology in the land administration of DKI Jakarta.